Modulation of a transient K+ current in the pleural sensory neurons of Aplysia by serotonin and cAMP: implications for spike broadening. - Hochner, B (1992)
To study the contribution of cAMP to the spike broadening produced by serotonin (5-HT) in the pleural sensory neurons of the tail withdrawal reflex, we utilized two phosphodiesterase-resistant cAMP analogs: the Sp diastereomer of cyclic adenosine 3',5'-monophosphothioate (Sp-cAMP[S]), which activates protein kinase A, and the antagonist Rp diastereomer of cyclic adenosine 3',5'-monophosphothioate (Rp-cAMP[S]), agonist Sp-cAMP[S] was injected into the sensory neurons, it caused spike broadening comparable to that induced by 5-HT. In turn, the cAMP antagonist Rp-cAMP[S] blocked approximately 50% of the 5-HT-induced spike broadening. We next examined the K+ currents that are modulated by 5-HT and determined how these currents are affected by cAMP. Confirming Baxter and Byrne [(1989) J. Neurophysiol. 62, 665-679], we found that 5-HT modulated two currents, an S-type K+ current (IKS) as well as a transient and voltage-dependent K+ current (IKV). Rp-cAMP[S] blocked the reduction by 5-HT of the early phase of IKV in parallel with, and to the same degree (60%), as this inhibitor blocked the IKS and spike broadening. These results support the idea that in the pleural sensory neurons cAMP mediates a significant part of the spike broadening that accompanies short-term facilitation produced by 5-HT and that cAMP can produce spike broadening by modulating both IKV and IKS.